The Regulation of the British securities industry : a selection of papers, edited and updated to 2 April 1979, from the first annual conference of the British Institute of Securities Laws, held at the London Hilton in November 1978 and organised by Investment and Property Studies Limited, London - Rider, Barry Alexander K.; British Institute of Securities Laws.; Investment and Property Studies Limited (London : Oyez Publishing, 1979)
This book is based on a selection of papers delivered at the first Annual Conference Of The British Institute of Securities Laws, which was held in London Hilton on 21 and 22 Of November 1978.
Includes bibliographical references.
oif 06/03/2019
Loans
Keywords: Securities industry; Stock exchanges--Law and legislation